ANAK TUHAN ALAY: Pengkhotbah 11 : 9 – 10 menilai Pergaulan Alay ala Generasi Muda Gereja - Doys Ivone Salakory (TANGKOLEH PUTAI, 2019)
The formation and development of a person's character is greatly influenced by the environment. The young generation is currently faced with one of the challenges, namely the phenomenon of alay in their surroundings. The alay phenomenon has a positive but also negative impact on the young generation of the church in living their lives as God's children. This paper intends to show the reflection effort of Ecclesiastes 11: 9-10 on the phenomenon of alay in the association of the young church generation as a reality.